Generating a Lighting System by Using Pico Hydro System - G. Subhashini; Devindran Munandy; Raed Abdulla (Universitas Ahmad Dahlan, 2017)
The main aim of this research is to design and develop LED based lighting system by using Pico hydro power. The proposed system is to use renewable energy to generate power in remote areas. The system is designed in a small scale which capable of lighting up a LED and sustain power when turbine stop to rotate. Reaction turbine is selected to be the suitable model for this Pico Hydro System (PHS). The performance of the system is tested by changing the materials for the blades and determines the suitable number of blades for the system to perform at maximum efficiency. Additional features, such as displaying generated voltage and flow rate has been implemented. It is observed that, the system could generate maximum voltage of 5.46V at the head height of 65 cm with flow rate of 5.51 L/Min. A total of 4.62 watt of net electrical power generated from this PHS, the value is obtained by using theoretical calculation. Finally, the system proves to be efficient in terms of generated voltage and cost, as compared to the journals which is reviewed in the literature. The scale of the design has to be remodified to be implemented in river areas.